Examining the effectiveness of the Engineering Launch program for first-year engineering students - Yang, Yang; Betz, Amy; Spencer, Craig (My University, 2022)
Motivation and Background: This COMPLETE EVIDENCE-BASED PRACTICE PAPER examines whether participating in the Engineering Launch program at a large Midwestern land- grant university influences the academic readiness of engineering students before they enter Calculus I course. Many students enrolled in Calculus I are not prepared for it. The remedial program Engineering Launch aims to improve students’ math preparation in Trigonometry, Algebra I, Geometry, and Algebra II, and bridge the perceived gaps in math preparation to get students ready for Calculus I. Many universities around the country have implemented similar remedial programs. There are two common approaches. One is a workshop-style course which typically requires weekly class time in addition to regular lectures [1]. The other is to offer a bridge course before the semester starts, with duration from one-week long [2] to several weeks [3, 4] These programs have shown positive results by increasing student pass rates in Calculus. The Engineering Launch program takes the second approach by offering a summer bridge course prior to the fall semester. This course is offered as a zero-credit hour course, which consists of a three-week online component and several in-person events the week before classes start. The course combines both synchronous and asynchronous math instruction. All instruction and module content is provided and delivered by a seasoned Calculus I instructor, who has over 15 years of experience teaching courses in calculus sequence. The course also includes one-on-one tutoring from a GTA in the Department of Mathematics. Learning about the usefulness of the Engineering Launch program can inform researchers, instructors, and administrators how to improve the readiness of first year engineering students in Calculus I and make it an effective approach in helping engineering students succeed academically.